Bumiputra SMES food manufactures halal certification challenges: a review - Hj. Pakir, Mohamed Ismail K. P.; Wan Yusoff, Wan Fauziah; Raja Mohd Rasi, Raja Zuraidah (American Scientific Publishers, 2018)
The concept of halal is associated with food products which are of high quality in terms of cleanliness, sanitation and compliance with Islamic law. In Malaysia Jakim is given a mandate by government of Malaysia to monitor and certify food industries with Halal certificates. In 2014, among the 828 Malaysian exporters of halal products, only 92 or 11% of the companies were bumiputra-owned. Also it is reported that 90% of Small Medium Enterprises (SMEs) owned by bumiputra operates without a halal certificate. They in fact did not apply for the halal certificate and did not display the halal logo. With an annual trade value of US$2.77 trillion for halal global market, there is essential for Malaysian bumiputra SMEs to acquired halal certificates in order to capture the vast opportunity offered by global halal market. This paper is to review halal development and challenges faced by Malaysian bumiputra SMEs food manufacturers in getting halal certificate. It is hope that future steps can be implemented to enhance the performance of bumiputra SMEs in Malaysia.